The Inspirational Women Religious Leader in Peace-building Viewed from the Concept of Multicultural Education (A case study in Salatiga as the second most tolerant city in Indonesia) - aprilian ria adisti (PAX HUMANA, 2020)
Women in this era have the same role and function as men in peace-building. It is an effort to realize the values, attitudes or behavior, and ways of life that support life peacefully.  The survey showed that women are more tolerant of differences and relatively have no tendency to use violence against groups compared to men. They have abilities to unite the differences, lead nonviolent community, mobilize peace communities, as well as their engagement with the theological aspects of gender roles in peace. This is a descriptive qualitative research which focused on exposing the role of the inspirational women religious leader in peace-building and how they teach multicultural education to their followers. Moreover, the Krathwohl Taxonomy is used to analyze the findings. The result shows that the three of inspirational women religious leader are able to introduce multicultural education through internalize the value of peace, such as inter-religious harmony, religious moderation and the value of tolerance based on their own respective religions, namely Islam, Buddhism and Christianity.Keywords: women, leader, peace-building, multicultural, education